Competition in times of crisis: Reflections from COVID-19 - Mena Labarthe, Carlos (2020)
Competition agencies are facing an unprecedented scenario as a result of the COVID-19 pandemic. Different from other economic crises, the COVID-19 health crisis has also brought new conditions of social organization with a direct impact on competition policy enforcement. These extraordinary circumstances have brought important considerations for competition law and policy. In Mexico, among other issues, these circumstances have confirmed the need to strengthen the interaction between the competition agency and other regulators, and to have more visibility the treatment of collaborations among competitors. This experience, certainly, represents an opportunity to reconsider key issues that will have an impact on the development of competition policy and competition law.